Paradox Aesthetics Blangkon In Yogyakarta And Surakarta - Rofingah, Ema Iis (KnE Social Sciences, 2017)
Mataram kingdom became part of the history of Kraton Yogyakarta, starting from the Giyanti agreement in 1755. Then Mataram kingdom was divided into two regions Solo and Yogyakarta. Each region was headed by one king. The title for the king's Solo palace is Pakubuwono, while the term for the king's palace in Yogyakarta is Hamengkubowono. One of the relics from the palace, which is still preserved until now is blangkon. Blangkon is used as a headgear by the people in the palace. Yogyakarta Blangkon style is different from Solo blangkon style, although this palace used to be one area. Blangkon have a specific pattern that is related to the lifestyle of Javanese community, especially people of the palace. Blangkon is considered as one of artifacts as it has a philosophy of characteristics and identity of Javanese community. This research used qualitative research in the form of literature study. The method used by the authors is by collecting data source: primary data and secondary data. Blangkon will be examined through the used patterns which is connected in the aesthetic paradox. Basically there are kinds of pattern which are called pattern two, three, four, and five. Eventually it came to a conclusion that Blangkon is the development of aesthetic paradox patterns of patterns three to five patterns. Keywords: Paradox aesthetics, Blangkon